Teacher Competence Development through In-House Training and Cooperative Learning: Pengembangan Kompetensi Guru melalui In-House Training dan Pembelajaran Kooperatif - Siska, Eka Usbika; Ishartiwi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Inclusive education ensures equal learning opportunities for all students, including those with special needs (SEN). Specific Background: Teachers in remote schools often lack knowledge and practical skills to design inclusive learning modules. Knowledge Gap: Few studies explore how school-based professional development improves teacher competence in remote 3T areas. Aims: This study aims to develop teacher competence in creating inclusive learning modules through In-House Training (IHT) integrated with Cooperative Learning at SD Negeri 11 Sandaran. Results: Conducted as School Action Research in two cycles with 10 teachers, the program improved cognitive, psychomotor, and affective-collaborative competencies. Teacher competence scores increased from 30% to 62%, and teachers demonstrated better differentiation of learning goals, use of Jigsaw and Think-Pair-Share strategies, and adaptation of teaching materials for SEN students. Novelty: This study provides rare evidence of successful teacher competence development in a 3T setting using a combined IHT and Cooperative Learning approach. Implications: The findings may serve as a reference for inclusive education strategies in other rural or under-resourced schools, supporting the design of contextually relevant professional development models. Highlights: Teacher competence improved across cognitive, psychomotor, and collaborative domains. Learning modules became more adaptive and inclusive after two training cycles. IHT combined with cooperative learning proved applicable even in remote 3T schools. Keywords: Inclusive Education, Teacher Competence, In-House Training, Cooperative Learning, Learning Module Design